The best of brochure design 12 - Public (Firm) (Beverly, Massachusetts Rockport Publishers, 2013)
"A well-executed brochure allows multiple facets of a company's personality to shine. The format forms and informs the narrative. The pacing and rhythm shape the experience. Brochures feature and showcase not only design and brand but photographers, illustrators, writers, fonts, materials, texture, and color -- the art and craft of printing"
Keywords: Brochures -- Design; Pamphlets -- Design; Advertising fliers -- Design